2019
DOI: 10.3168/jds.2018-15108
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-221 regulates proliferation of bovine mammary gland epithelial cells by targeting the STAT5a and IRS1 genes

Abstract: MicroRNAs (miRNA) play an essential role in mammary gland development and lactation. Previous studies in cattle have shown that miR-221 is highly expressed in peak compared with early lactation. However, the functions of miR-221 in bovine mammary gland epithelial cells and the mechanisms by which this miRNA affects cell proliferation and milk synthesis remain unclear. We hypothesized that miR-221 targets and modulates the expression of specific genes in the Janus kinase-signal transducer and activator of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…Therefore, our results indicate that miR-143 might promote milk fat synthesis by affecting the expression of the key regulators of lipid accumulation in BMECs. miRNAs can regulate multiple target genes, and exert their biological functions by different target genes in different cell types or in different cell states of the same cell type [30,31]. Chen et al [32] and Kim et al [33] revealed that miR-143 promotes adipogenesis by interacting with MAP2K5 and Pre-f-1 in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our results indicate that miR-143 might promote milk fat synthesis by affecting the expression of the key regulators of lipid accumulation in BMECs. miRNAs can regulate multiple target genes, and exert their biological functions by different target genes in different cell types or in different cell states of the same cell type [30,31]. Chen et al [32] and Kim et al [33] revealed that miR-143 promotes adipogenesis by interacting with MAP2K5 and Pre-f-1 in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs can regulate multiple target genes, and exert their biological functions by different target genes in different cell types or in different cell states of the same cell type [ 30 , 31 ]. Chen et al [ 32 ] and Kim et al [ 33 ] revealed that miR-143 promotes adipogenesis by interacting with MAP2K5 and Pre-f-1 in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Transfection of miR-221, which is highly expressed at peak compared with early lactation [101], into cultured bovine mammary gland epithelial cells inhibits cell proliferation and reduces the viability of these cells [155]. Dual luciferase assays have revealed that Stat5a, Stat3, and Insulin receptor substrate 1 (Irs1), key genes in the PI3KAkt/mTOR and JAK-STAT signalling pathways, bind directly to miR-221.…”
Section: Roles Of Mirnas In Mammary Gland Developmentmentioning
confidence: 99%
“…The bovine mammary epithelial cell line was used to explore the function and regulatory mechanism of lncRNA and miRNA. It was obtained from the primary bovine mammary alveolar cells by stable transfection with SV-40 T antigen [33] and cultured in a 1:1 mixture of Ham's F-12 and Dulbecco's modi ed eagle medium (DMEM) supplemented with 10% heat-inactivated fetal bovine serum (FBS) and 1% penicillin-streptomycin according to Jiao et al [34]. LncRNA MPNCR overexpression plasmid vector, miR-31 mimic or inhibitor were transfected using Lipofectamine 2000 (Invitrogen, Carlsbad, CA, USA) according to the manufacturer's instructions when the cells were at 60-80% con uence.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%